THE BEAUTY OF TABANAN AS AN INSPIRATION FOR INTERIOR DESIGN AESTHETIC ELEMENTS - Ni Ketut Rika Primadewi; Ni Made Leony Savitri Wirasa; I Putu Udiyana Wasista (Journal of Aesthetics, Design, and Art Management, 2022)
Purpose: This paper examines the potential advantages possessed by Tabanan Regency in terms of natural wealth, cultural diversity, preservation of history, and traditions that can be used as objects of creative exploration in forming a design of aesthetic elements by taking into account local cultural identity. Research methods: The design method is used as a guide in designing. The stages consist of inspiration, ideation, and implementation. Findings: From mountains, rice plants, dances, to porcelain plates, they can be used as inspiration for interior decoration. All of them are used as dynamic aesthetic elements and represent the beauty of Tabanan Regency. Implications: The potential for culture, art, and nature in Tabanan Regency, can be used as endless inspiration as design objects. It takes creativity and sensitivity in exploring it. Thus, this can be a way to preserve the beauty of culture, nature, and art in an area.